Desenvolvimento de critério objetivo para a sinalização da ingestão alimentar deficiente de paciente hospitalizado - Silva, Anne Rocha Faria [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
Considerando que durante o período de internação hospitalar ocorre um agravamento do quadro nutricional dos pacientes, a presente pesquisa foi realizada visando a criação, implantação e validação de um critério objetivo de sinalização da diminuição da ingestão alimentar de pacientes hospitalizados, para a intervenção imediata pelo profissional de nutrição O trabalho foi realizado em hospital geral, com capacidade para 190 pacientes e com uma ocupação média de 60% dos leitos e se desenvolveu nas alas de internação de pacientes do Sistema Único de Saúde. O Serviço de Nutrição e Dietética do hospital conta com 27 funcionários, sendo dois nutricionistas, um para a área de produção e outro para dietoterapia. Para a implantação do sistema de sinalização, foi necessário, primeiro realizar a adequação do cardápio e a escolha do ponto de corte, que servia como sinalizador de ingestão inadequada e motivo de intervenção do profissional da nutrição e, posteriormente, treinamento das copeiras. Estipulou-se, com base nas referências adotadas, uma resto-ingestão de 50% como ponto de corte, a partir do qual as copeiras deveriam sinalizar. As copeiras foram treinadas...

Considering that during hospitalization an aggravation of the nutritional picture of the patients occurs, the present research was developed, toward the creation, implementation, and validation of an objective criterion for signaling the reduction of alimentary ingestion by hospitalized patients for the immediate intervention on the part of the nutrition professional. The work was carried out in a general hospital, with capacity for 190 patients and an average occupation of 60% of the beds in the sections of the Sistema Único de Saúde (Only System of Health). The Dietary Nutrition Service has 27 employees, including two nutritionists: one for the production area, and the other for diet therapy. For the implementation of the signaling system, it was first necessary to make the adequacy of the meal and the selection of the cut point, used as indicator of an inadequate ingestion, and the rationale for the nutrition professional intervention, after this the employees were trained. Based on the adopted references, it was stipulated that a 50% remaining portion ingestion would serve as the cut point, from which the employees (kitchen staff) would have to signal. The employees were trained for standardized assembly of the trays, as well as visual recognition of the cut point ingestion rate. The signaling was made in the Dietary Prescription Sheet, proper of the hospital, using a small circle for breakfast and snack, and an x for lunch and dinner.
Keywords: Ingestão alimentar; Intervenção nutricional